Walking as a research modality: the three paths of Francesco Careri in São Paulo - SP - Frascareli, Marina Biazotto; Fiorin, Evandro (Revista Nacional de Gerenciamento de Cidades, 2022)
This article approaches walking as a research modality in São Paulo from the analysis of tree paths by the italian architect Francesco Careri carried out in the capital of São Paulo at diferent times. In this sense, the text written through na analysis of the practice od the patch taken in the Comunidade de São Francisco (Zona Leste), in Praça Victor Civita (Zona Oeste) and in Bixiga (Centro). In this way, the main objective of this article is to reconstruct the path of the italian architect in the city of São Paulo, as well as to analyze his experiences, relating them to work in his book: Walkscapes: o caminhar como prática estética (2013) and Caminhar e Parar (2017), thus detailing this type of research in São Paulo.